Utilisation en formation de professeurs des écoles d'un outil métalinguistique destiné aux élèves de cycle 3 - Lionel Audion (Nantes Université, 2016)
In 2014, Maria Pilar Ric, Eliane Sanz-Lecina and Claudine Garcia-Debanc had a training module, based on the comparison of languages, designed for trainee teachers and emphasized the difficulty in changing the design of the teaching the language, very stereotypical, among future teachers. We made the same observation and propose another way to pass the primary school teachers metalinguistic posture, which we consider to Marie-Laure Elalouf, Claudie Péret and Patrice Gourdet (2016) as a prerequisite. It has been known since Chervel (1997 and 2006) that the grammar school is an object built by the school; Yet the language sciences, in the twentieth century, proposed new more logical theories to account for the functioning of the language. This is why many educationalists, following the call of the "Pratiques" Review (special issue, 1979) there are thirty-five, calling for a reorganization or a "didactic reconfiguration" of the study of language as recalled Vargas (2014). It is difficult to educate future teachers to remote linguistic theories of their performances. For these reasons, it seemed appropriate to involve us, as an experiment, three young teachers in training our research to show that it is possible to transpose (Chevallard, 1985) in primary education theories language deemed difficult, as the theory of enunciative operations (Antoine Culioli). By testing tools in their classrooms forged during our doctoral research, young teachers take ownership of the concepts better than if we tried to explain the theory, which is verified by interviews and questionnaires conducted three recent years with teachers holders and trained otherwise. This approach is based on that proposed by Cèbe & Goigoux to design didactic artifacts (2007).